Views of cancer patients regarding cardiopulmonary resuscitation in Greece. (19th April 2018) - Miaris, N.; Samantas, E.; Siafaka, I.; Logothetis, E.; Iacovidou, N.; Chalkias, A.; Xanthos, T.
Abstract : Cardiopulmonary resuscitation (CPR) in patients with cancer is an ethical issue of worldwide interest. A questionnaire‐based study was carried out in a Greek oncology hospital aiming to explore the attitude of Greek cancer patients towards CPR. Overall, 200 patients (94 male, 106 female) of a mean age of 62.8 years took part in the study. Only 42 (21%) patients indicated that they knew what CPR really involves and only 20 (10%) patients thought that CPR has serious side effects, while the mean estimated in‐hospital CPR survival rate to hospital discharge was 56.6% (minimum = 2%, maximum = 99%, standard deviation [ SD ] = 25.16) and 42.1% (minimum = 0%, maximum = 90%, SD = 24.56%) in case of unselected and cancer patients respectively. Despite their poor knowledge, 177 (88.5%) patients were willing to undergo CPR in case of an in‐hospital arrest, 127 (63.5%) thought that they had the right to choose their CPR status and 141 (70.5%) believed that they should be asked about it when they enter the hospital. Most patients (36%) wanted their CPR status to be decided by themselves, their family and their doctor jointly. These findings indicate that specific measures should be applied to clinical practice in order to best manage this ethical issue, and consequently, improve cancer care.